Turkish Politics and Policies under the Impact of the 1980's PKK Revolt and the Gulf War of the Early 1990s - Canci, Haldun; Sen, Sevket Serkan (Cambridge Univ Press, 2012)
This article examines Turkish politics and policies during the 1980s and 1990s in light of occurrences in Turkey and neighboring states, with particular attention to the impact of the 1980's PKK revolt and the outbreak of the Gulf War in 1990. In doing so, it outlines the political debates among the major political parties and the perspectives of the Turkish army generals on the important political issues of the period. These events, and those of the subsequent decade, have led to the emergence of a new status quo in Turkey that has had major political and economic repercussions.
Keywords: Terrorism; Turkey